2017
DOI: 10.1016/j.fertnstert.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum galectin-9 as a noninvasive biomarker for the detection of endometriosis and pelvic pain or infertility-related gynecologic disorders

Abstract: Our results suggest that Gal-9 could be a promising noninvasive biomarker of endometriosis and a predictor of various infertility or pelvic pain-related gynecologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 51 publications
(52 reference statements)
5
43
1
Order By: Relevance
“…However, surgery is a highly invasive procedure with potential risks. Although several studies have found several biomarkers in endometriosis, a definite diagnostic biomarker is not yet available [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, surgery is a highly invasive procedure with potential risks. Although several studies have found several biomarkers in endometriosis, a definite diagnostic biomarker is not yet available [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It affects 6%–10% of women of reproductive age (Burney and Giudice, 2012; Laux-Biehlmann et al, 2015). The common symptoms of endometriosis are pain and subfertility (Brubel et al, 2017; Righarts et al, 2018). Pain symptoms associated with endometriosis include dysmenorrhea, dyspareunia, dysuria, dyschezia, and chronic pelvic pain, which profoundly affect quality of life (Simoens et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using a GalPharma (GalP) ELISA, we have reported that the concentration of Gal-9 in the blood fluctuates rapidly, reflecting the pathological conditions of patients with various diseases [8][9][10][11][12][13][14][15][16][17]. Similar disease-related fluctuations have been reported using both independently developed and commercially produced ELISAs [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. When the reported Gal-9 concentrations were compared, a large divergence was observed in the results, even within healthy control groups, with values ranging from 0 to 26, 560 pg/mL.…”
Section: Introductionmentioning
confidence: 54%